Development Analysis of Chili Imports in East Java - Setyaningtyas, Megawati Mahardika Rizky; Widayanti, Sri; Mubarokah, Mubarokah; Wijayati, Prasmita Dian (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2022)
East Java Province is one of the leading national chili producers. But, East Java still imports chilies to meet fluctuating demand and prices. The variables of imports, production, consumption, pricing, and currency rates were employed in this study and ranged from 2019 to 2021. This study aims to forecast the volume of chili imports in East Java for the next year (12 months) and analyze the factors that influence chili imports in East Java to determine the most dominant influencing factors. The method used in this study is (Autoregressive Integrated Moving Average) ARIMA model and multiple linear regression analysis. The results of the study show: The development of chili imports in East Java in the prediction results with the ARIMA model (1,1,1) shows that chili imports have a downward trend, and simultaneously chili imports are influenced by production, consumption, price, and exchange rate, with consumption as the most dominant factor. It is hoped that the government will regulate the volume of imports by imposing import quotas and controlling chili prices